2018
DOI: 10.1098/rsos.172417
|View full text |Cite
|
Sign up to set email alerts
|

Filtration-induced production of conductive/robust Cu films on cellulose paper by low-temperature sintering in air

Abstract: Cellulose paper is an attractive substrate for paper electronics because of its advantages of flexibility, biodegradability, easy incorporation into composites, low cost and eco-friendliness. However, the micrometre-sized pores of cellulose paper make robust/conductive films difficult to deposit onto its surface from metal-nanoparticle-based inks. We developed a Cu-based composite ink to deposit conductive Cu films onto cellulose paper via low-temperature sintering in air. The Cu-based inks consisted of a meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In addition, a binder effect was caused by the Cu particles decomposed from the self-reductive Cu complex connected to the Cu flakes. Sakurai et al further modified the mixed paste of the CuF–AmIP complex and Cu flake for the production of highly conductive Cu films on cellulose paper for air atmosphere-sintering [ 140 ]. The Cu flakes were immersed in formic acid to remove the surface oxide layers from the Cu flake.…”
Section: Formulation Designs In Cu-based Mixed Inks/pastesmentioning
confidence: 99%
“…In addition, a binder effect was caused by the Cu particles decomposed from the self-reductive Cu complex connected to the Cu flakes. Sakurai et al further modified the mixed paste of the CuF–AmIP complex and Cu flake for the production of highly conductive Cu films on cellulose paper for air atmosphere-sintering [ 140 ]. The Cu flakes were immersed in formic acid to remove the surface oxide layers from the Cu flake.…”
Section: Formulation Designs In Cu-based Mixed Inks/pastesmentioning
confidence: 99%
“…The film resistance of the conductive cellulosic materials was affected by the degree of copper electroplating, and the resistance was at the range between 16.5 and 369.3 Ω/sq. In other work, Cu was deposited on a cellulose surface, yielding a conductive material with high flexibility (Sakurai et al 2018).…”
Section: Agmentioning
confidence: 99%
“…This approach was explained most clearly by Mamunya et al (2002), who showed how metal powders deposited onto larger nonconducting elongated particles can serve as conducting elements as core-shell structures. More typically, conductive materials have been applied to coat cellulosic surfaces by adsorption or particle deposition from solution (Hu et al 2009;Zhou et al 2014;Shi et al 2015;Meulendijks et al 2017;Sakurai et al 2018;Wang et al 2018a). For example, Meulendijks et al (2017) prepared cellulose nanocrystals to which silver particles has been applied to the surface by in-situ precipitation.…”
Section: Coating the Cellulosementioning
confidence: 99%
“…To date, a variety of chemical/physical approaches have been suggested to endow metallic printed features with high conductivity. Most importantly, from the viewpoint of cost-effectiveness, much recent efforts have been devoted to developing inexpensive Cu conductors. It has been demonstrated that a critical disadvantage of printable Cu nanoparticles (NPs), namely, unpredictable oxidation behavior during sintering in air, can be overcome by the use of instantaneous optical sintering processes. One such process, flash-light-sintering (FLS) in a timescale of 10 –3 s, has opened up a new possibility of generating highly functioning Cu conductors with its facile capability for high-throughput production. The recent efforts of incorporating the chemical moieties triggering a chemical reduction at low temperatures has provided a possibility of generating the Cu conductors by a conventional thermal sintering process in air. In this methodology, the complicated reactions including densification, oxidation, and reduction reactions are associated with each another in a simple thermal annealing process, so that the electrical properties of the resulting conductors are highly dependent on the processing parameters of temperature and time. …”
Section: Introductionmentioning
confidence: 99%